Run rules schemes for statistical process monitoring: a literature review. Issue 1 (2nd January 2023) - Jalilibal, Zahra; Karavigh, Mohammad Hassan Ahmadi; Amiri, Amirhossein; Khoo, Michael B. C.
ABSTRACT: Different control charts are developed for monitoring various types of quality characteristics in the area of Statistical Process Monitoring (SPM). Moreover, new techniques are proposed to improve the performances of the suggested control charts. One of the popular techniques for this purpose is run rules. These rules increase the sensitivity of control charts in detecting different shift sizes, especially small and medium shifts. In this paper, a content analysis (based on 100 papers in this area from 1955 to 2020) is conducted to (i) classify the articles that employed run rules in SPM, (ii) recognize the research gaps and (iii) provide guidance to motivate future research in this area.